As tecnologias digitais da informação e comunicação na formação inicial dos professores de matemática na Universidade Federal do Pará - BARROS, Marlon Augusto das Chagas (2023)
Digital Information and Communication technologies are increasingly present in our daily lives, being indispensable tools for our different technologies and advances that promote the possibility of change in various sectors of society, including education. In this work, we seek to analyze whether, in the opinion of the graduating students, the Mathematics Licentiate Course at the Federal University of Pará enabled them to use Information and Communication Technologies in their professional activities. To this end, the pedagogical project of the course was analyzed in order to observe aspects related to the digital environment in initial training. In addition, a survey was conducted with senior students in order to obtain their opinion about their initial training process.